2017
DOI: 10.1177/0009922817744607
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Fecal Calprotectin in Evaluation of Chronic Gastrointestinal Symptoms in Primary Care

Abstract: Fecal calprotectin (FC) is a marker of intestinal inflammation. Data are limited on utility of routine FC testing in pediatric primary care. Participants 0 to 18 years old who had an FC test in the years 2010-2014 were retrospectively identified. Those with less than a year of follow-up or a prior diagnosis of inflammatory bowel disease (IBD) were excluded. In all, 84% (689/822) had normal FC; no participant with normal FC was diagnosed with IBD in the subsequent 12 months. Also, 16% (133/822) had elevated FC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…8 A study of routine data from an American health plans database of FC testing for chronic gastrointestinal symptoms in primary care suggests that it is used in routine general practice in at least one other country. 9 The NICE recommendations were based on an evaluation of secondary care test accuracy studies and assumptions that referral decisions would follow FC test results. This resulted in a slow uptake and inconsistent use of FC testing in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…8 A study of routine data from an American health plans database of FC testing for chronic gastrointestinal symptoms in primary care suggests that it is used in routine general practice in at least one other country. 9 The NICE recommendations were based on an evaluation of secondary care test accuracy studies and assumptions that referral decisions would follow FC test results. This resulted in a slow uptake and inconsistent use of FC testing in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, FC is found to be a far superior test than standard blood tests (albumin, ESR, CRP, hemoglobin, white cell count or platelet count) in diagnosing IBD among children suspected of having IBD (15). A number of studies have evaluated the usefulness of FC in the primary-care setting where IBD can be safely excluded and avoid unnecessary referrals or endoscopy (16)(17)(18). The most recent study by Walker et al (18) demonstrated that a FC >100 µg/g is able to fully discriminate (100% sensitivity) children with IBD from those who do not have IBD in a primarycare setting.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 898 patients, none of whom had a diagnosis of IBD and all of whom had fecal calprotectin measured in the primary care setting, 84% had normal calprotectin levels. 8 None of these patients were diagnosed with IBD or any other GI disease in the following 12 months. 8 These and other data suggest that fecal calprotectin is an excellent screening tool for IBD and can help avoid unnecessary referrals and endoscopies.…”
Section: Shelly Deanmentioning
confidence: 99%
“…7 In a number of prospective studies performed in different clinical settings, the sensitivity of a positive fecal calprotectin for IBD approaches 100%. 8 If the fecal calprotectin level is low (,15.6), the negative predictive value for IBD approaches 100%. 8 The specificity and positive predictive value of a positive test result is much lower because there are a variety of other etiologies for intestinal inflammation besides IBD.…”
Section: Shelly Deanmentioning
confidence: 99%
See 1 more Smart Citation